Traditional versus virtual learning: How engaged are the students in learning English literature? - Halili, Siti Hajar; Rahman, Nurul Hanani Abdul; Razak, Rafiza Abdul (Indonesia University of Education, 2018)
This study is aimed to investigate students' levels of engagement in learning English literature for traditional learning and virtual learning environment. There are four dimensions of engagement that were studied, which are the cognitive, behavioural, emotional and agentic engagement. A self-determination theory perspective on student engagement by Reeve (2012) was used for the foundation of this study. A questionnaire of School Engagement Measure was used to collect data from 80 respondents. The data were analysed using descriptive analysis utilizing the SPSS software. The results of this study show that the engagement level of the virtual learning environment is higher than the engagement level of the traditional learning. Based on the results, further research is recommended to focus on the effectiveness of virtual learning environment in the classroom for the teaching and learning process.